Lithuania’s, Latvia’s and Japan’s Climate Policies. Are we Far from the Ideals of the Paris Agreement? - Sabūnas Audrius (Environmental and Climate Technologies)
The study compares the most recent developments in energy policies in Japan, Lithuania, and Latvia to mitigate climate change, indicating the most problematic parts and highlighting the areas where all three could collaborate. The ambition of each country is estimated by the submitted Intended Nationally Determined Contributions (INDCs), the legal framework for addressing climate change, the trends in energy intensity, and the penetration of the non-fossil fuel sector, comparing them with a common goal to become carbon neutral by 2050 and whether they abide by the recommendations by IPCC. The methodology is based on a literature review and data analysis of the three countries. In addition to the political will, the study also considers external factors such as the impact of the COVID-19 pandemic and the Russian invasion of Ukraine on climate change mitigation policies. Therefore, this study offers a comprehensive outlook of the things to be achieved so that all three countries would become role models to follow in climate policy. It fosters a viewpoint that each country needs to develop and constantly improve its climate change policies. The national targets must be continuously reviewed and updated to close the ambition and implementation gaps. The study also attempts to discuss Japan’s differing approaches regarding the role of modern technologies and a green economy compared to Latvia and Lithuania. In addition, increasingly demanding ambitions will be needed as decarbonisation remains too slow in the three countries and globally.